Cooperation in the Fieid of Criminal Justice: "Vertical" and "Horizontal" Models - N. A. Safarov (Московский журнал международного права, 2007)
In order to prosecute crimes under their jurisdictions international criminal tribunals need to provide effective legal assistance to states on matters of arrest and surrender of accused, investigations, production of evidence and etc. Without the help of national authorities international tribunals cannot operate effectively. But at the same time, the mechanisms of cooperation with international courts are based on specific rules, which are closely connected with the mode of establishment of international criminal tribunals, whether on the basis of UN SC Resolutions (ad hoc tribunals) or international treaty (International Criminal Court).Moreover the establishment of international criminal tribunals (ICT ad hoc and ICC) introduced in international practice new forms of cooperation, which seriously differ from traditional forms of cooperation between states, named as mutual legal assistance in criminal matters. In this regard, the new concept of so-called "vertical" and "horizontal" cooperation, which was introduced by the ICTY Appeals Chamber in the Blaskic subpoena case, was very important for the differentiation of various forms of cooperation. Under the "horizontal" (inter-state) model, the assistance relationships are based on principle of equality of sovereign states (par in parem non habet imperium). The "vertical" (supra-state) model implies that cooperation between states and international criminal tribunals fundamentally differs from traditional inter-state cooperation. The "vertical" model does not envisage application of the principle of reciprocity and grounds on which assistance may be refused (ad hoc tribunals) or minimizes the possibility of such refusal (ICC).Thus, the present article attempts to analyze main features of both models of cooperation applied in modern international criminal law.